Icariside II improves myocardial fibrosis in spontaneously hypertensive rats by inhibiting collagen synthesis. (9th December 2019) - Fu, Shu; Li, Yeli; Wu, Yuting; Yue, Yun; Yang, Danli
Abstract: Objectives: We aimed to investigate the effects of icariside II (ICS II) on myocardial fibrosis in spontaneously hypertensive rats (SHRs) and to explore the possible mechanisms. Methods: We used SHRs as animal models, and we administered ICS II (4, 8 or 16 mg/kg) orally by gavage for 12 consecutive weeks (Fu et al., Biomed Pharmacother 2018; 100: 64). The left ventricular morphology of the rats was observed using haematoxylin–eosin (HE) staining. The occurrence of myocardial interstitial fibrosis was detected by Masson's trichrome staining. The protein levels of alpha smooth muscle actin (α-SMA), Collagen I, III, matrix metalloproteinases 2 and 9 (MMP-2 and MMP-9, respectively), tissue inhibitor of metalloproteinase 1 (TIMP-1), transforming growth factor-β1 (TGF-β1), phospho-Smad2 (p-Smad2), phospho-Smad3 (p-Smad3) and phospho-p38 (p-p38) were examined by Western blotting. Key findings: The results suggested that ICS II improved myocardial interstitial and perivascular collagen deposition and decreased Collagen I/III and α-SMA expression. ICS II (8 and 16 mg/kg) downregulated the expression of MMP-2 and MMP9 and upregulated the expression of TIMP1. In addition, the protein levels of p-Smad2/3, TGF-β1 and p-p38 were decreased by ICS II treatment. Conclusions: The results suggest that ICS II can inhibit the expression of Collagen I and Collagen III through the MMP/TIMP-1 and TGF-β1/Smad2, 3/p-p38 signalling pathways and that it has therapeutic effects on myocardial fibrosis.